2009
DOI: 10.2337/dc08-0472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parental Type 2 Diabetes on Offspring With Type 1 Diabetes

Abstract: OBJECTIVE -The purpose of this study was to study the association between a parental history of type 2 diabetes and the metabolic profile as well as the presence of the metabolic syndrome and diabetes complications in patients with type 1 diabetes.RESEARCH DESIGN AND METHODS -This was a cross-sectional study design in 1,860 patients with type 1 diabetes from the Finnish Diabetic Nephropathy (FinnDiane) Study (620 patients with and 1,240 age-matched patients without a parental history of type 2 diabetes). Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 26 publications
8
35
0
1
Order By: Relevance
“…Specifically, we showed that subjects in the DCCT with parents with T2DM gained more weight with INT, had higher waist circumferences and insulin doses, and had lipid levels consistent with MetS. 12 These findings were confirmed in an independent cohort of patients with T1DM 32 and shown to be predictive of CAD in another observational cohort. 33 In the present analysis, increasing prevalence of individual family histories of diabetes, hypertension, and hyperlipidemia in DCCT were associated with increased IMT with INT during EDIC.…”
Section: Discussionmentioning
confidence: 60%
“…Specifically, we showed that subjects in the DCCT with parents with T2DM gained more weight with INT, had higher waist circumferences and insulin doses, and had lipid levels consistent with MetS. 12 These findings were confirmed in an independent cohort of patients with T1DM 32 and shown to be predictive of CAD in another observational cohort. 33 In the present analysis, increasing prevalence of individual family histories of diabetes, hypertension, and hyperlipidemia in DCCT were associated with increased IMT with INT during EDIC.…”
Section: Discussionmentioning
confidence: 60%
“…Because our main objective was to examine the effects of exposure of offspring to maternal diabetes during gestation, the focus was on the presence or absence of diabetes rather than type. Correct ascertainment of parental dysglycemia is supported both by prior studies demonstrating validity of diabetes history by questionnaire (7,19) and by the fact that birth weights of offspring from mothers with diabetes during pregnancy were increased as expected. Future studies that would distinguish the effects on offspring according to parental diabetes type would be of interest.…”
Section: Discussionmentioning
confidence: 83%
“…A small number of articles (n = 7) were also excluded for various reasons, including studies that were restricted to the enrolment of participants with genetic susceptibility to type 1 diabetes (human leukocyte antigen [HLA]), studies in which the outcome was islet autoimmunity rather than T1DM, a study that only reported the risk of DM, a study in which the onset of T1DM was not reported, or one study that had overlap of the patient population with another included study . Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis. Of these, 12 were case‐control studies, eight were cohort studies, and one was a cross sectional study .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis. Of these, 12 were case‐control studies, eight were cohort studies, and one was a cross sectional study . The characteristics of the included studies are summarized in Tables S1 ‐ S3.…”
Section: Resultsmentioning
confidence: 99%